HR 12995, A Bill, To Amend The Internal Revenue Code Of 1954 To Tax Cigarettes On The Basis Of Their Tar And Nicotine Content (Tufts Archival Research Center, 2007)
Bill to amend the Internal Revenue Code of 1954 to tax cigarettes based on their tar and nicotine content. Specifies length, weight and nicotine conditions for each tax increase.